2020
DOI: 10.1016/j.scib.2019.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Tunable magnetism of a single-carbon vacancy in graphene

Abstract: Removing a single-carbon vacancy introduces (quasi-)localized states for both  and  electrons in graphene. Interactions between the localized  dangling bond and quasilocalized  electrons of a single-carbon vacancy in graphene are predicted to control its magnetism. However, experimentally confirming this prediction through manipulating the interactions between the  and  electrons remains an outstanding challenge. Here we report the manipulation of magnetism of individual single-carbon vacancy in graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…Note that all our calculations in this region produce non-magnetic solutions. Any potential magnetic solution, however, is expected to be close in energy, as past DFT calculations on graphene with a monovacancy without 5CB suggests that the largest energy difference between a magnetic and the non-magnetic solution is of the order 3 × 10 −2 eV [ 60 ]. As 5CB reaches its physisorbed state at 1.61 Å above the monovacancy the overall energy lowers by nearly −7 × 10 −2 eV ( Figure 4 inset).…”
Section: Resultsmentioning
confidence: 99%
“…Note that all our calculations in this region produce non-magnetic solutions. Any potential magnetic solution, however, is expected to be close in energy, as past DFT calculations on graphene with a monovacancy without 5CB suggests that the largest energy difference between a magnetic and the non-magnetic solution is of the order 3 × 10 −2 eV [ 60 ]. As 5CB reaches its physisorbed state at 1.61 Å above the monovacancy the overall energy lowers by nearly −7 × 10 −2 eV ( Figure 4 inset).…”
Section: Resultsmentioning
confidence: 99%
“…289,323,324 After that, in 2016, Zhang et al successfully provided direct experimental evidence of π magnetism induced by a single carbon vacancy in graphene, using a scanning tunneling microscope (STM). 322 They also showed that the splitting of the vacancy-induced graphene state is quite robust in both n-and p-type doping graphene.…”
Section: Metal-free Two-dimensional Spintronic Systemmentioning
confidence: 98%
“…Defects are always crucial to change the material properties in two dimensional systems. Vacancy can induce magnetism in case of graphene [17,18] but only the vacancy cannot induce it in MoS 2 [19,20]. In case of phosphorene, neither monovacancy nor strain alone can create magnetism, however, the interplay between monovacancy and the strain is able to induce effective magnetization in phospherene [21].…”
Section: Introductionmentioning
confidence: 99%